MANAJEMEN SUMBER DAYA MANUSIA TENAGA ADMINISTRASI FAKULTAS DALAM MENDUKUNG EFEKTIVITAS LAYANAN AKADEMIK: STUDI KUALITATIF PADA UIN IMAM BONJOL PADANG (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2026)
The effectiveness of academic services in higher education is shaped not only by administrative procedures but also by the quality of human resource management behind those procedures. This article analyzes human resource management among administrative staff at the Faculty of Adab and Humanities, UIN Imam Bonjol Padang, by positioning document handling as a work context rather than the main object of inquiry. The study employed a descriptive qualitative approach using interviews, observation, and documentation. Informants were selected through purposive and snowball techniques, involving administrative leaders, administrative staff, and service users. Data were analyzed through reduction, display, conclusion drawing, and source triangulation. The findings reveal five core issues: partial mismatch between educational background and job competency requirements, limited continuous technical training, increased administrative workload due to manual work systems, suboptimal work facilities, and the need for competency-based HR planning. The study indicates that administrative service problems should be interpreted as issues of job design, competency development, and organizational support. The article proposes a human resource management model consisting of competency mapping, continuous training, workload redesign, digital work support, and measurable service performance indicators.